Ginsenoside Rg3 Inhibits Migration and Invasion of Nasopharyngeal Carcinoma Cells and Suppresses Epithelial Mesenchymal Transition - Wang, Dingkun (Biomed Res Int, 2019)
Nasopharyngeal carcinoma (NPC) is a highly invasive and metastatic head and neck cancer. Distant metastasis becomes the predominant mode of treatment failure in NPC patients. Ginsenoside Rg3 (Rg3), an active pharmaceutical component extracted from traditional Chinese medicine ginseng, shows antitumor effects in various cancers. In this study, we aimed to determine whether Rg3 inhibits the migration and invasion activity of NPC cells and to explore the possible mechanisms. Our results revealed that Rg3 hampers cell migration and invasion in both HNE1 and CNE2 cell lines. A reduced level of matrix metalloproteinase-2 (MMP-2) and MMP-9 was induced by Rg3 treatment. In addition, Rg3 significantly altered the expression of epithelial mesenchymal transition (EMT) markers with increased E-cadherin but decreased Vimentin and N-cadherin expression. Transforming growth factor β- (TGF-β-) induced morphological transition and marker proteins change of EMT were reversed by Rg3. What is more, Rg3 suppressed the expression of EMT-related transcription factors, especially the Zinc Finger E-Box Binding Homeobox 1 (ZEB1). In summary, our data suggested that Rg3 could inhibit migration and invasion of NPC cells. This effect of Rg3 might be mediated through regulating MMP-2 and MMP-9 expressions and suppressing EMT. Thus, Rg3 may be a potentially effective agent for the treatment of NPC.